Member - Chrysostomou, Christis (My University, 2026)
Appointed by the Cyprus Organization for Standardization as a representative of Cyprus in SC8 which is the committee developing the European Standard for Earthquake Resistant Design (ΕΝ 1998). The appointment is valid to date